Chapter 8 Constructing a Wider View on Memory Beyond the Dichotomy of Field and Observer Perspectives - Peeters, Anco (Taylor & Francis, 2023)
Memory perspectives on past events allegedly take one of two shapes. In field memories, we recall episodes from a first-person point of view, while in observer memories, we look at a past scene from a third-person perspective. But this mere visuospatial dichotomy faces several practical and conceptual challenges. First, this binary distinction is not exhaustive. Second, this characterization insufficiently accounts for the phenomenology of observer memories. Third, the focus on the visual aspect of memory perspective neglects emotional, agential, and self-related social aspects. Fourth, the focus on the time of recall neglects the fact that visual, emotional, agential, and social aspects of perspective can also be dissociated in the original experience. In this chapter, we move away from the standard visual dichotomy. Instead, we propose that memory perspective is better understood along four lines: visual, agential, emotional, and social. Drawing on empirical research, we argue that these dimensions predict a disposition to recall a past event based on the present situation of the memorizer. This account supports seeing episodic memory as a natural kind, supported by scenario construction mechanisms and minimal memory traces. By remapping the classic distinction between field and observer perspectives along four dimensions, our proposal provides explanatory advantages and secures practical gains by enabling testable hypotheses.